Vaccination in rheumatology: the present and prospects - Boris Sergeyevich Belov; G M Tarasova; M S Naumtseva (Современная ревматология, 2012)
In modern rheumatology, comorbid infections (CIs) have a great impact on morbidity and mortality, in systemic connective tissue diseases in particular. In this connection, much attention is given to the intense introduction of different vaccines into rheumatological care. Much evidence suggests that immunization has no negative influence on the course of the underlying rheumatic disease (RD). The efficiency and safety of vaccination to prevent respiratory tract infections as the most important CIs are demonstrated. The fundamentals of the EULAR vaccination guidelines and the key areas of future investigations into this problem are presented.